Draft Special Component Plan 1989-90 Union Territory of Pondicherry - Planning Commission (Planning Commission, 1989)
The Union Territory of Pondicherry consists of four regions, namely, Pondicherry, Karaikal, Mahe and Yanam lying geographically isolated from one another. Pondicherry region which is on the east coast about 160 Kms. South o f Madras is the largest of these and consists o f 12 scattered areas interspersed with enclaves of South Arcot District of Tamil Nadu. Karaikal region is about 140 Kms.
Government of Pondicherry, Planning and Research Department